The Analysis of Types And Voices of The Sentences In Lembar Kerja Siswa (Students’Worksheet) For Grade 8 - Afifa Sulam Zulfikar; Sirotul Mila; Trikaloka Handayani Putri (Journal of Research in Foreign Language Teaching (JRFLT), 2021)
In supporting student teaching and learning activities at school, there are several tools used, one of which is the students’ worksheet (LKS). This kind of tool is commonly chosen because it is considered more practical and more affordable in terms of price. Because of its wide usage, it is necessary to analyze the suitability of the worksheet for thelearning process. This research aims to find out the types and voices of the sentences in the students' worksheet (LKS) Interactive English, Workbook for Junior High School Year VIII first semester 2013 Curriculum Revised Edition, and its relevance with the characteristics of emergent readers. This current study applied descriptive qualitativewith content analysis. The data were the sentences in reading and dialogue texts collected from the English worksheet especially declarative and interrogative sentences, Interactive English Workbook for Junior High School Year VIII first semester 2013 Curriculum Revised Edition. The result showed that most of the sentences were simple sentences and the voices of the sentence were active voices. The dominance of simple sentences and active voice were relevant to the characteristics of emergent readers. Therefore it is suggested that the LKS be used in the learning process for the students in grade 8 of Junior High School.